The effect of social media engagement and product quality on purchase decisions with brand trust as an intervening variable - Muhammad Adlian Kautsar; Christina Dewi Wulandari; Poso Nugroho; Tri Damayanti (Privietlab, 2025)
The energy industry, particularly the fuel sector, plays a vital role in supporting Indonesia's economy. Factors such as social media engagement, product quality, and brand trust influence consumers’ purchasing decisions. This study aimed to analyze the direct and indirect effects of social media engagement variables and product quality on purchasing decisions, with brand trust as an intervening variable for PT Shell Indonesia products. The analysis method in this study uses quantitative primary data, and the test stages carried out are the convergent validity, discriminant validity, reliability, R-square, goodness of fit, and path coefficient tests. The data used in this study were collected using a questionnaire instrument, and the valid data collected were from 120 respondents. The sampling method in this study was non-probability sampling with a purposive sampling technique. The testing tool used was Smart PLS. The results showed that Social Media Engagement and Product Quality variables had a direct and indirect effect on Brand Trust and Purchase Decision variables. However, Brand Trust had no direct effect on the Purchasing Decision variable.